Strategy of Non-Formal Education Development Through Entrepreneurial Skills at CLC Budi Utama Surabaya - Widodo, Widodo; Darmawanti, Ira; Kharisma, Novia Nur (Universitas Negeri Semarang, 2021)
The development of urban community needs for increasing self-competence is a great opportunity for Non-Formal Education (NFE), but the NFE program organized by Community Learning Centre (CLC) has not been able to answer. It needs the right strategy to develop NFE programs that are in accordance with the needs of urban communities, namely entrepreneurship. The research objective was to reveal the urban area entrepreneurship based NFE program development strategy carried out by CLC. The research used a descriptive qualitative approach, with the following research results. Entrepreneurship-based NFE program development strategy through stages; (1) strategy formulation which includes activities to identify potentials, formulate the vision, mission and objectives of the CLC institution, identify internal and external conditions of the CLC institution, select strategies, formulate strategies. (2) Implementation of culinary entrepreneurship strategies with attention to urban problems, effective organizational structures, marketing programs, budgets, developing management information systems, and linking with performance. (3) Evaluation of culinary entrepreneurship strategies; the effectiveness of the process and the achievement of results, namely the learning community has skills as a provision for entrepreneurship. This NFE program management strategy can solve the problem of unemployment, and for CLC institutions to develop and become independent. The conclusion is that the strategy of developing the NFE program based on entrepreneurial skills can create graduates who are ready to become entrepreneurs. So that graduates can provide benefits for their own life and social environment.